PERLINDUNGAN HUKUM PENGAMBILALIHAN (AKUISISI) PERSEROAN TERBATAS BAGI PEMEGANG SAHAM MINORITAS - Irawati, Irawati (Fakultas Hukum, Universitas Diponegoro, 2017)
Limited Company is a legal subject. Regulations on limited liability company are generally regulated in Act Number 40 of 2007 About Limited Company. The establishment of special arrangements concerning the Company is to protect the interests of shareholders and creditors, as well as other related parties and the interests of the company itself. To create a healthy and efficient business climate, among others, can be pursued by merger, merger and takeover of limited liability company. The presence of minority shareholders is not only protected in the interests of ownership of shares, but also has an important function in decision making at the General Meeting of Shareholders. In terms of legal minority shareholders need special attention and treatment that can be realized one of them with Apprisal Right. Keywords : Limited Company,Takeover, Minority Shareholder.